2015
DOI: 10.1007/s11094-015-1230-z
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Polyalkylguanidine Hydrochloride Copolymers and Their Antibacterial Activity Against Conditionally Pathogenic Microorganisms Bacillus Cereus and Escherichia Coli

Abstract: Copolymers based on aliphatic diamines of various methylene chain lengths and guanidine hydrochloride were prepared by polycondensation in the melt. Antibacterial activity of water-soluble copolymers based on guanidine against conditionally pathogenic microorganisms Escherichia coli and Bacillus cereus was evaluated using diffusion in agar. A relationship was found between the ratio of the number of hydrophobic methylene groups to the number of ionized guanidines and the antibacterial activity of the copolymer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 11 publications
1
8
0
2
Order By: Relevance
“…7 . It can be seen that sole polyguanidine with a concentration of 5.0 mg mL −1 presented an inhibition zone of 14 mm in diameter, which is almost the same as that reported by Grigor'eva et al 27 On the other hand, the Fe 3 O 4 nanoparticles exhibited no antibacterial activity. The synthesized Fe 3 O 4 /polyguanidine nanocomposite had a relatively high antibacterial effect, presenting an inhibition zone of about 10 mm when the concentration was 5.0 mg mL −1 .…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…7 . It can be seen that sole polyguanidine with a concentration of 5.0 mg mL −1 presented an inhibition zone of 14 mm in diameter, which is almost the same as that reported by Grigor'eva et al 27 On the other hand, the Fe 3 O 4 nanoparticles exhibited no antibacterial activity. The synthesized Fe 3 O 4 /polyguanidine nanocomposite had a relatively high antibacterial effect, presenting an inhibition zone of about 10 mm when the concentration was 5.0 mg mL −1 .…”
Section: Resultssupporting
confidence: 86%
“…The broad peak at around 3449 cm −1 of Fe 3 O 4 was also displaced to 3408 cm −1 because of the overlap with the peak of the N–H vibration from polyguanidine. 27 …”
Section: Resultsmentioning
confidence: 99%
“…При этомв качестве последних, могут быть применены как одноклеточные, так и более высокоорга-низованные организмы (планктон, грибы, растения, рыбы, птицы, крысы и другие млекопитающие) [1][2][3][4][5][6][7]. Но, хотя использование для целей биотестирования многоклеточных организмов позволяет более адек-ватно моделировать с их помощью человеческий организм, это делает проведение таких анализов значи-тельно более сложным, дорогим, длительным и субъективным в оценке результатов.…”
Section: аннотацияunclassified
“…As drug carriers, polymer hydrogels have gained increasing interest [4][5][6][7]. There has been tremendous interest in polyguanidines because of their high antibacterial properties, low toxicity and ability to form highly swollen hydrogels that can be complexed [8][9][10][11]. In our previous study, we demonstrated that the gels exhibit wound-healing effects comparable to those of widely used chloramphenicol and methyluracil preparations [12,13].…”
Section: Introductionmentioning
confidence: 99%